Nickel chelation therapy as an approach to combat multi-drug resistant enteric pathogens - Stéphane L. Benoit (Nature Portfolio, 2019)
Abstract The nickel (Ni)-specific chelator dimethylglyoxime (DMG) has been used for many years to detect, quantitate or decrease Ni levels in various environments. Addition of DMG at millimolar levels has a bacteriostatic effect on some enteric pathogens, including multidrug resistant (MDR) strains of Salmonella Typhimurium and Klebsiella pneumoniae. DMG inhibited activity of two Ni-containing enzymes, Salmonella hydrogenase and Klebsiella urease. Oral delivery of nontoxic levels of DMG to mice previously inoculated with S. Typhimurium led to a 50% survival rate, while 100% of infected mice in the no-DMG control group succumbed to salmonellosis. Pathogen colonization numbers from livers and spleens of mice were 10- fold reduced by DMG treatment of the Salmonella-infected mice. Using Nuclear Magnetic Resonance, we were able to detect DMG in the livers of DMG-(orally) treated mice. Inoculation of Galleria mellonella (wax moth) larvae with DMG prior to injection of either MDR K. pneumoniae or MDR S. Typhimurium led to 40% and 60% survival, respectively, compared to 100% mortality of larvae infected with either pathogen, but without prior DMG administration. Our results suggest that DMG-mediated Ni-chelation could provide a novel approach to combat enteric pathogens, including recalcitrant multi-drug resistant strains.